THE EFFECT OF ANIMATION VIDEO-BASED HEALTH EDUCATION ON ADOLESCENTS' KNOWLEDGE ABOUT HIV/AIDS - Robbani, Muhammad Fikri; Rahman, Irpan Ali; Gunawan, Asep (Indonesian Journal of Health Science, 2025)
The prevalence of HIV/AIDS in the world has reached 38.4 million, including adolescents and adults. During adolescence, to grow and develop with good health, teenagers need information, including health education, to strengthen their understanding of health problems such as HIV/AIDS. The aim of this research is to determine the effect of animated video-based health education on adolescents' knowledge about HIV/AIDS. The research design uses a pre-experimental design with one group pretest posttest. The population is all teenage students at MAN 2 Ciamis school, totaling 644 respondents. This sampling method uses Non Probability Sampling Purposive Sampling with a sample size of 87 respondents. The sampling technique uses the Slovin formula and measuring instruments in the form of questionnaires whose validity has been tested. The statistical test used is the Wilcoxon Sign Rank Test. The results of the research before being given animated video-based health education showed that 38 respondents (43.7%) were in the poor category, but after being given animated video-based health education, 73 respondents increased to the good category. respondents (83.9%), based on the Wilcoxon Sign Rank statistical test, it showed a significant p-value = 0.000 < 0.05. There is an influence of animated video-based health education on teenagers' knowledge